EVALUASI PEMBERIAN PAKAN BUATAN TERHADAP PERTUMBUHAN BENIH IKAN MARU (Channa marulioides) SEBAGAI UPAYA DOMESTIKASI AWAL - Hylda Khairah Putri; Amal Jr, Muchlisul; Setiawan, Agus; Sarmila; Farid Mudlofar; Sri Warastuti (Journal of Fish Nutrition, 2025)
The maru fish, Channa marulioides, is one of the native fish species of Indonesia that inhabits the Kapuas River in West Kalimantan. In addition to being consumed by local people, maru fish also has an export market as an ornamental fish. The market demand for maru fish is still met from wild catches. Excessive exploitation and a lack of environmental carrying capacity will increasingly threaten the existence of the maru fish in the wild. The continuous population decline can lead to the extinction of fish species. Therefore, before extinction, domestication needs to be carried out through cultivation activities. Currently, the alternative feed commonly used in the maintenance of maru fish seeds is dry maggots. However, maggots have not been optimally used as the main feed. This study aims to evaluate the substitution of dry maggots with commercial pellets in maru fish seeds as an initial domestication effort. Maru fish seed maintenance was carried out for 90 days. The seeds come from natural catches in the Kapuas River, West Kalimantan. The study was conducted experimentally using a Completely Randomized Design (CRD). The treatment in this study was a combination of dry maggots and pellets. Treatment M100 (100 % dry maggot), Treatment M75P25 (75 % dry maggot + 25 % pellets), Treatment M50P50 (50 % dry maggot + 50 % pellets) and Treatment M25P75 (25 % dry maggot + 75 % pellets). Each treatment was repeated three times. The results showed that seeds maintained with 50 % dry maggot + 50 % pellet feed had the lowest final growth, final growth rate, feed efficiency and FCR compared to other treatments.